Sosialisasi Literasi Digital dan Analisis Data Psikologis Siswa SMK Menggunakan Metode Naive Bayes Berbasis Website - Yusuf, Dede; Mayji Danardono; Dinar Danan Sukmawati; Tri Stiyo Famuji; Raden Bagus Bambang Sumantri; Walidy Rahman Hakim (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2026)
Advances in information technology require vocational school students to possess strong digital literacy skills and be aware of their psychological well-being. This community service activity was conducted at SMK Muhammadiyah Karangpucung as part of the TMMD program, a collaboration between Al-Irsyad University Cilacap (UNAIC) and the Indonesian National Armed Forces (TNI). This program aims to improve digital literacy understanding and introduce the use of website-based psychological analysis technology with the Naive Bayes algorithm. This algorithm functions to process student psychological assessment data and classify them into interest and talent categories based on the highest probability, so that the results obtained are more measurable and objective. Based on the pretest evaluation, only 30% of students correctly understood their interests and talents based on self-assessment. After participating in digital literacy socialization and training on the use of the Naive Bayes-based psychological analysis system, posttest scores increased to 90% of students who had identified their interests and talents based on the recommendations of the system analysis results. This indicates a significant increase in students' understanding of scientific interest and talent mapping assisted by digital technology. This activity serves as a concrete example of synergy between universities, defense institutions, and vocational schools in building an educational ecosystem that is adaptive to technology and supports ongoing monitoring of students' psychological well-being.